Kapasitas Tampung (Carrying Capacity) Hijauan Makanan Ternak (HMT) - Riswan Riswan; Heny Vensye Saiya; Irine Ike Praptiwi (Universitas Musamus, Merauke, Papua, 2018)
This research aims to know the carrying capacity, vegetation, feed production getation, and drymatter of forages Tanah Miring district, Merauke Regency. The research was conducted by gatheringprimary data in Tanah Miring District, for 2 months. Feed sample collected by purposive samplingwith quadran 1m. The result showed, Tanah Miring Disctrict, had 5 potential forages, they were :Paspalum conjugatum with the sar 15,28 % , Paspalum cartilagneum with the SDR 6,29 % , Neptuniaoleraceae with the SDR 8.38 % , Fimbristylis dichotoma with the SDR 4,72 % , and Cyperus halpannwith the SDR 4,46 % , But high potentially as forage is a species of Paspalum conjugatum.Composition botany found in the field grazing were 55 kind of vegetation consist of 29 kind of toragegrass , 2 kinds of legume and 24 forage other. Carring capacity forage based on production drymatter (BK) as many as 5.928,39 kg per hectare/year, so in one hectare can accommodate 2.2 ST.Based on material fresh matter get 118.666,5 kg per hectare/year, can accommodate 1,32 ST/hectare